2021
DOI: 10.1038/s41420-021-00632-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-139-5p sponged by LncRNA NEAT1 regulates liver fibrosis via targeting β-catenin/SOX9/TGF-β1 pathway

Abstract: Liver fibrosis is a patho-physiological process which can develop into cirrhosis, and hepatic carcinoma without intervention. Our study extensively investigated the mechanisms of lncRNA NEAT1 and miR-139-5p in regulating liver fibrosis progression. Our results demonstrated that the expression of lncRNA NEAT1 was increased and the expression of miR-139-5p was decreased in fibrotic liver tissues. LncRNA NEAT1 could sponge miR-139-5p and promoted hepatic stellate cells (HSCs) activation by directly inhibiting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Such phenomenon was counteracted by TGF-β3, suggesting that Vgll3, a member of lncRNA, could promote the progression of cardiac fibrosis by activating the TGF-β3-related pathways ( Stawowy et al, 2004 ). Being different from the above studies, lncRNA nuclear enriched abundant transcript 1 (NEAT1) is closely associated with the progression of lung, liver, and kidney fibrosis ( Wang et al, 2019a ; Wang et al, 2021b ; Zhao et al, 2022 ). As reported, NEAT1 was significantly expressed in both HF patients and TAC-induced HF mouse models, inhibition of its expression attenuated the TGF-β1-induced cardiac fibrosis, GSK126 (an EZH2 inhibitor) weakened TGF-β1-induced downregulation of Smad7 expression and upregulation of p-Smad2/3, and upregulation of Smad7 reversed the cardiac fibrosis caused by NEAT1 over-expression ( Zhang et al, 2020b ).…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...mentioning
confidence: 79%
“…Such phenomenon was counteracted by TGF-β3, suggesting that Vgll3, a member of lncRNA, could promote the progression of cardiac fibrosis by activating the TGF-β3-related pathways ( Stawowy et al, 2004 ). Being different from the above studies, lncRNA nuclear enriched abundant transcript 1 (NEAT1) is closely associated with the progression of lung, liver, and kidney fibrosis ( Wang et al, 2019a ; Wang et al, 2021b ; Zhao et al, 2022 ). As reported, NEAT1 was significantly expressed in both HF patients and TAC-induced HF mouse models, inhibition of its expression attenuated the TGF-β1-induced cardiac fibrosis, GSK126 (an EZH2 inhibitor) weakened TGF-β1-induced downregulation of Smad7 expression and upregulation of p-Smad2/3, and upregulation of Smad7 reversed the cardiac fibrosis caused by NEAT1 over-expression ( Zhang et al, 2020b ).…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...mentioning
confidence: 79%
“…[ 23 ] LncRNA NEAT1 was also upregulated in liver fibrosis and activated HSCs via sponging of miR‐139‐5p. [ 24 ] Our previous study found that Kcnq1ot1 is highly expressed in liver cirrhosis. [ 16 ] The present study showed that BMSCs treatment can downregulate Kcnq1ot1 expression in cirrhotic mouse models both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Different forms of ncRNAs may work together to have a synergistic effect in the pathogenesis and progression of liver fibrosis. For example, lncRNA nuclear enriched abundant transcript1 (lncRNA NEAT1) and miR-139-5p have a synergistic effect that exacerbates the development of liver fibrosis[ 30 ]. Another study has revealed that lncRNA metastasis-associated lung adenocarcinoma transcript1 (lncRNA MALAT1) upregulates expression of β-catenin and promotes liver fibrosis through the Wnt/β-catenin pathway[ 31 ].…”
Section: Ncrnas In the Pathogenesis And Progression Of Liver Fibrosismentioning
confidence: 99%